Quando o petr?leo empobrece - Costa, Mahysa Ferreira (2019)
The present study aimed to access and investigate the native microbial diversity present in the mangrove soil in order to serve as a reference study for further work, so far, no analysis of the microbial genetic diversity of the mangrove sediments of the rio Santar?m, Floresta Atl?ntica, of the Ecopolo III - APA do Partigi has been reported in the literature. Therefore, from the survey of the native microbial diversity in a mangrove environment, through the new generation of massive sequencing, the determination of the organic material contents and the analysis of HTPs, we obtained results that demonstrate a greater abundance of the Proteobacteria phylum, followed by the Chloroflexi phylum, where the presence of these groups of microorganisms in the sediment may indicate the occurrence of recent or historical hydrocarbon contamination. The study area in question is influenced by the Camamu Basin estuary and its geographical location draws attention to its vulnerability to the impacts of oil spills, in addition to being an Environmental Protection Area (APA). Thus, the present study also evaluated the structure and diversity of autochthonous microbial community exposed to oil from the Rec?ncavo basin by amplifying the V4 region of the 16S rRNA gene using the NGS Illumina platform through a laboratory disturbance experiment, where the effect of this variable on microbial groups would be analyzed for a period of 30 days. From the results generated, we noticed the significant growth of the Proteobacteria group, which may indicate the presence of groups that have metabolic function for bioremediation, besides the laboratory experiment demonstrating the depletion of bacterial cells after 30 days of oil contact under the community microbial. Given what was observed through this study, the structure and diversity of the native microbial community of the Santar?m river mangrove sediment are negatively affected by the occurrence of the oil spill.